Between European Rationality and Eastern Spirituality: A Deconstruction of Identity and Modernity in Tawfiq Al-Hakim's Novel 'Uṣfūr Min Al-Syarq - Jumriyah Jumriyah; Mubasyiroh Mubasyiroh; Siti Fatimah; Muhammad Zakki Masykur (Journal of Arabic Literature (JaLi), 2026)
This article examines ʿUṣfūr min al-Sharq by Tawfiq al-Hakim as a dialectical exploration of European rationality and Eastern spirituality within the discourse of modernity. Modernity is frequently framed in binary terms: the West as rational, material, and technologically advanced, and the East as spiritual and tradition-bound. Such dichotomies, however, often overlook how identity is constructed and negotiated in modern Arabic literature. While previous scholarship has read the novel through the lens of civilizational conflict, it has seldom undertaken a deconstructive analysis of how East–West identities are destabilized and reconfigured through the characters' existential struggles. This study addresses two questions: (1) how are European rationality and Eastern spirituality narratively constructed in the novel, and (2) how are identity and modernity dismantled through the characters' inner conflicts and relationships? Employing qualitative interpretive literary analysis informed by Derridean deconstruction and postcolonial theory, the article traces the text's ambivalent and paradoxical structures of meaning. The findings show that the protagonist Muhsin's dialogues with the Russian intellectual Ivan expose the existential emptiness of a Western rationality that excludes the transcendent from its account of the world, while Muhsin's admission of a faith as fragile and wavering as a flower in the wind reveals Eastern spirituality to be equally unstable once subjected to modern rationalization. Through the Opera scene—where Muhsin's aesthetic and emotional response is set against Ivan's disillusioned critique of Europe—the novel reframes modernity not as a fixed Western achievement but as a hybrid third space of identity negotiation. The study contributes a deconstructive rereading that moves beyond the civilizational-conflict paradigm, demonstrating how al-Hakim's narrative unsettles the very binary it appears to stage.